Comparative clinical performance of stainless steel, zirconia, and Bioflx crowns in primary molars: a randomized controlled trial - Ahmed Abdelhafez; Vineet Dhar (BMC Oral Health)
Abstract Background Choosing the appropriate crown type for primary molars is essential for effective restoration and oral health. Stainless steel crowns are durable and cost-effective, making them suitable for extensive decay. Zirconia crowns offer esthetic advantages, while Bioflx crowns require less preparation and provide optimal appearance. Understanding the benefits and limitations of each type ensures optimal outcomes for young patients. The purpose of the study was to clinically compare these three types of crowns for primary molars regarding plaque accumulation, debonding rate, crown substance loss and gingival health. Materials and methods Registered with clinicalTrials.gov (NCT06706167), this study included 75 children (43 males, 32 females; mean age: 6.3 years) divided into 3 groups: Group A (stainless steel crowns), Group B (zirconia crowns), and Group C (Bioflx crowns), with 25 patients each. Plaque index, crown survival regarding debonding rate and substance loss, and gingival index were evaluated at baseline, 6, and 12 months. Results At 6- and 12-month follow-ups, no significant differences were observed among groups. However, zirconia crown demonstrated better results in terms of plaque accumulation and gingival health. Conversely, stainless steel crown showed marginally better performance in crown retention. Conclusion All crowns showed acceptable clinical performance. Factors such as crown retention, esthetics and biocompatibility should be considered when selecting the most appropriate crown for each molar. Trial registration The study was registered on ClinicalTrials.gov, with the registration number NCT06706167 with registration date 26,112,024.